CT-guided Lung Fine Needle Aspiration Biopsy: Analysis of Efficacy, Yield and Intricacies - Nair, Anirudh V; Anirudh, Soumya; Moorthy, Srikanth; Cyril, P; Rajamma, Bindhu Mangalath; Ramachandran, PV (Indian Journal of Medical and Paediatric Oncology, 2018)
Aim: This study aims to evaluate various factors that affect the cytological yield while performing computed tomography (CT) guided lung fine needle aspiration biopsy and to determine the complication rate of this procedure. Materials and Methods: In this cross sectional study, we analyzed 70 patients undergoing CT-guided transthoracic lung fine-needle aspiration biopsy (FNAB). 22-gauge spinal needle was used in sixty patients and 20-gauge in ten patients. The presence and absence of an onsite cytopathologist affecting the adequacy of yield for a conclusive cytodiagnosis was compared in groups of 35 patients each. The incidence of complications such as pneumothorax, pulmonary hemorrhage was recorded. Results: Cytological yield was adequate for a conclusive cytodiagnosis in 59 cases (84.2%). Thirty-seven cases (52.8%) were malignant with adenocarcinoma (70.2%) being the most common, 22 cases (31.4%) had benign etiology. Cytological yield was adequate for a conclusive diagnosis in the group (n = 35) with an onsite cytopathologist (100%) compared with those cases without an onsite cytopathologist (68.6%) (P = 0.005). Pneumothorax was observed in 16 cases (22.8%), the incidence of pneumothorax was higher when there was an intervening parenchyma (P = 0.005). Conclusion: CT-guided transthoracic FNAB is an accurate method to rule out malignancy with a reasonable rate of complications. The presence of an onsite-cytopathologist significantly improves the adequacy of yield for a conclusive cytodiagnosis, and should be routinely employed. Pneumothorax and pulmonary hemorrhage are the most common complications as a result of FNAB. The incidence of pneumothorax is higher when there is intervening lung parenchyma.
Keywords: Computed tomography; cytopathologist; fine-needle aspiration biopsy; lung cancer